Emotions and the therapist : a systematic-dialogical approach - Bertrando, Paolo (Systemic thinking and practice series., 2015)
In recent years, systemic theory and practice adopted a dialogical orientation, centred on the persons of the therapist and client. This has led to a growing attention toward emotions, which, in this book, is developed in terms of emotional systems. An emotional system in therapy may be viewed as the sum of the emotions existing and interacting in people's lives. Relevant changes in life happen when emotional stances and sequences change within the system, leading, for example, to a greater sense of agency or hope, or to a different perception of the situation. This book looks at emotions within human systems in terms of dominant and silent emotions, which shape and are shaped by human relationships, and may be played in several ways according to reciprocal emotional positioning. The therapist uses his or her own feeling, and understanding of the emotions within the therapeutic dialogue, in order to create hypotheses and new dialogues which allow change,?rst of all, in the emotional tone and positioning of clients. The book deals with key therapeutic questions related to emotions: how can the therapist see clients in terms of emotional systems? How can the therapist develop a better understanding of his or her own emotional preferred positions? And how can he or she use such increased awareness of emotional facts to become more sensitive to clients' needs and wishes, in order to implement more ef?cient and comprehensive interventions?